Mechanical and physical properties of three Eucalyptus spp. clones planted in Thailand - Trairat Neimsuwan; Kitipong Tangkit; Chakrit Na Takuathung; Nopparat Kaakkurivaara; Ponthep Meunpong; Narinthorn Jumwong; Pattama Sangvisitpirom; Tomi Kaakkurivaara (Journal of Forest Science, 2024)
Eucalyptus plantations are an important source of raw materials for the Thai forest products industry. Despite its economic value, only a few noncomprehensive papers have been published about the wood properties and fungal susceptibility of eucalyptus. Our study covered the most commonly used commercial eucalyptus clones with a wide variety of sizes from eastern Thailand. We assumed that the properties of the clones would differ based on the tree sizes. The objectives of this study were to determine the effects of diameter at breast height (DBH), size, and clone type on wood properties and mould susceptibility. The optimal usage of each log characteristic based on the log quality and properties could be used to determine the maximum payoff. The wood properties and log characteristics of five eucalyptus log classes with three clones were investigated. In general, the levels of means and standard deviations were as follows: the modulus of rupture (MOR) was between 39 ± 4.9 MPa and 66 ± 5.4 MPa, and the modulus of elasticity (MOE) was between 14.5 ± 9.7 GPa and 24.0 ± 2.7 GPa. In addition, the compression parallel to the grain was between 28 ± 3.2 MPa and 43 ± 2.4 MPa, and the compression perpendicular to the grain was between 13 ± 0.7 MPa and 19 ± 1.1 MPa. The shear strength parallel to the grain was between 10 ± 0.3 MPa and 14 ± 0.6 MPa. The cleavage and hardness were from 4.7 ± 1.6 N to 7.4 ± 0.9 N and from 3.6 ± 0.3 kN to 6.2 ± 0.6 kN, respectively. The toughness and nail withdrawal were from 27.3 ± 3.5 kN.mm-1 to 50.5 ± 1.0 kN.mm-1 and from 28.56 ± 4.1 N.mm-1 to 34.52 ± 2.8 N.mm-1, respectively. Eucalyptus clone K7 had lower MOR and other mechanical properties than clones K58 and K62 except MOE. When DBH increased, the mechanical and physical property values increased as well. This happened for all clones, and especially when DBH was over 200 mm. The results of this study showed that log characteristics, such as taper, slenderness, and crookedness, should be used for log grading standards and that each fast-growing eucalyptus clone could be applied to different product classes.